Nostalgia, homesickness, and migration: A qualitative study into Polish migrant experience - Valentina Garro (Journal of Global Faultlines)
This study seeks to examine the relationship between nostalgia, homesickness, and the transnational interests of Polish migrants in the UK. This study observes several relationships between these experiences in Polish migrants, most notably how feelings of homesickness and nostalgia are linked to transnational interests. Qualitative research in the form of in-depth interviews with 10 Polish migrants living in London and Stoke-on-Trent, acquired mostly through snowball sampling, were conducted to capture the nuances of migrant experiences. This study also suggests areas for further research in migration studies, in particular the effect of migration circumstances on homesickness and nostalgia.